PELAKSANAAN PROGRAM PENINGKATAN KETAHANAN PANGAN DI KECAMATAN SABAK AUH KABUPATEN SIAK (STUDI KASUS TANAMAN PADI) - Muhammad Gustain; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
So that the problem in this case is How the security improvement program implementation in District Sabak Auh Siak in rice plants and Is factors that affect the implementation of the security improvement program in the District of Sabak Auh Siak in rice plants. From the results of research conducted on the Implementation of the Program for Increasing Food Security in the district of Sabak Auh Siak there are some identification problems that occur in rice crops in the district of Sabak AUH include: The transformation of land in the district of Sabak Auh obviously very big influence on the target surplus in Siak. Where formerly Siak a granary and the largest producer of rice in Riau which is 40,000 tons per year, but since the land use surplus is reduced, which in the year 2013 and only a 2000 tons only, absence of irrigation facilities in the district of Sabak Auh that resulting in reduced production of rice in Siak, Help tracktor from Siak district government that is not appropriate allocation, which should each farmer group get 2-3 tractors actually only got one machine tracktor.From the description above, the researcher is interested to take the title on the effect of "Food Security Enhancement Program Implementation in District Sabak Auh Siak (Case Study of Rice)".Keywords: Implementation, Program Improvement, Food Security